2017
DOI: 10.5398/medpet.2017.40.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Lactic Acid Bacteria with Cholesterol-Lowering Activity from Digestive Tracts of Indonesian Native Chickens

Abstract: The aim of the study was to identify the cholesterol-lowering activity of indigenous lactic acid bacteria isolated from the small intestine, cecum, and colon of Indonesian native chickens and evaluated for bile salt hydrolase (BSH) activity in vitro by using MRS media added taurodeoxycholic acid (TDCA) and CaCl 2 . The quantitative measurement of cholesterol-lowering activity of LAB was investigated by using soluble cholesterol containing MRS broth (100 µg/mL of cholesterin) and incubated at 37 °C for 48 h. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In the previous in vitro studies, we reported that both probiotics performed cholesterollowering activities (Julendra et al, 2017;Istiqomah et al, 2018). The cholesterol-lowering activities of L. plantarum AKK-30 and S. cerevisiae B-18 were 17.4% and 51.8% respectively (Table 2).…”
Section: Viability and Potency In Cholesterol-loweringmentioning
confidence: 87%
See 2 more Smart Citations
“…In the previous in vitro studies, we reported that both probiotics performed cholesterollowering activities (Julendra et al, 2017;Istiqomah et al, 2018). The cholesterol-lowering activities of L. plantarum AKK-30 and S. cerevisiae B-18 were 17.4% and 51.8% respectively (Table 2).…”
Section: Viability and Potency In Cholesterol-loweringmentioning
confidence: 87%
“…The binding of bile acids by β-glucans in the human intestine were able to eliminate in bile acid pool and improved cholesterol breakdown. In previous studies (Julendra et al, 2017;Istiqomah et al, 2018) found that viability and cholesterol lowering activity of S. cerevisiae B-18 was higher than L. plantarum AKK-30. Yalçın et al (2010) reported that supplementation of S. cerevisiae in diet reduced cholesterol content in blood and egg yolk of laying hens.…”
Section: Blood Biochemical Profilesmentioning
confidence: 94%
See 1 more Smart Citation
“…The Ca-lactic acid is seen as clear zones around the colony on the medium [19]. The present of CaCO3 in the growing medium is an early step of LAB detection, where LAB show clear zones after the incubation period [20].…”
Section: A Isolation Of Lab From Indigenous West Sumatera Fermented mentioning
confidence: 99%
“…Over the last decade, the investigation on the identification, characterization, and utilization of microbes isolated from GIT of chicken increased rapidly. Some of them reported the use of lactic acid bacteria as a probiotic agent for chicken (Musikasang et al, 2009;Damayanti et al, 2014;Jannah et al, 2017;Hamida et al, 2015;Yeh et al, 2017;Julendra et al, 2017). Meanwhile, the information about the lactic acid bacteria isolated from the GIT of Indonesian ducks for poultry probiotic agent is still limited.…”
Section: Introductionmentioning
confidence: 99%